Sepsis: older and newer concepts. Issue 3 (March 2016) - Vincent, Jean-Louis; Mira, Jean-Paul; Antonelli, Massimo
Summary: Sepsis is a common complication in patients in intensive care units and a frequent reason for intensive care unit admission. Sepsis is a major cause of morbidity and mortality and, without specific antisepsis therapies, management relies on infection control and organ support. For these interventions to be most effective, they must be started early, which highlights the need for all health-care workers to be aware of sepsis so that diagnosis can be made as early as possible. In this Viewpoint, we discuss some of the earlier terms used to characterise and define sepsis, and point out some of their limitations. We then introduce some aspects of new consensus definitions, proposed by an expert panel, which highlight in particular the importance of organ dysfunction. These definitions should help provide a more standardised approach to the identification of patients with suspected sepsis in both clinical practice and clinical research.